Adapting Reading Instruction to Meet the Needs of Nursing Students: Insights from a Targeted Educational Study - Amiroh, Rizqi; Mirizon, Soni; Eryansyah, Eryansyah (Universitas Hamzanwadi, 2024)
Developing Higher-Order Thinking Skills (HOTS) and effective information transfer is crucial for nursing students, impacting their academic and professional competence. This study aims to identify the gaps in English reading materials used by nursing students at a Health Polytechnic, assessing their adequacy in supporting these critical cognitive skills. The research focused on 79 second-semester nursing students during the 2022/2023 academic year and employed a 25-item questionnaire to analyze target situations, deficiencies, current situations, and strategies. The results reveal that existing general English coursebooks need to meet the specialized needs of nursing education. Notably, these materials lack content that promotes HOTS and aids in information transfer, essential elements for nurturing the cognitive and professional skills required in nursing. The study underscores a significant need for more appropriate materials that support HOTS, highlighting the need for strategically revised material development. It is recommended that custom English reading materials integrating HOTS and effective information transfer techniques be developed to enhance comprehension and relevance in the nursing curriculum, thereby better preparing nursing students for their future roles.